TRENDS OF DEVELOPMENT OF THE INSURANCE MARKET: NATIONAL AND WORLD ASPECTS - A. Sholoiko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The key indicators of development of the insurance market of Ukraine and foreign countries in the pre-crisis, crisis and post-crisis periods are considered. It is done to reveal basic national and world trends, make forecast of development of the domestic insurance market and give suggestions of the directions of improvement of functioning of the Ukrainian insurance market.